A Critical Exploration of Human-Primate Dynamics and Ecological Reflections in ‘Rise of the Planets of the Apes’ Movie: An Ecocriticism Literary Analysis - Zulkarnaen, Dicky Morgana; Saraun, Mychelle Ayde Abigail; Clara, Scarlet; Chendra, Rivalio; Pane, Charrine Sefanya Fiorentina Fiorentina (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2023)
This journal article offers an ecocritical analysis of the film